Blockchain Integration in Information Systems: A Systematic Review of Security, Efficiency, and Adoption Barriers - Mohammadi, Mohammad Qias; Kohistani, Ahmad Jaamay; Ghafori, Agha Mohammad; Fazil, Abdul Wajid (Transpublika Publisher, 2025)
Blockchain technology has emerged as a transformative innovation in information systems, offering enhanced security, efficiency, and transparency. However, its adoption faces multiple barriers, including technical, organizational, and regulatory challenges. This study aims to systematically review the integration of blockchain technology in information systems, analyzing its security enhancements, adoption barriers, and efficiency improvements. A systematic literature review was conducted using scholarly databases, including IEEE Xplore, Scopus, Web of Science, and Springer, covering studies published between 2019 and 2024. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology was applied to screen and select relevant studies. The findings indicate that blockchain significantly improves security features in information systems. For example, one study showed that blockchain’s cryptographic mechanisms reduced fraud rates by 30% in healthcare transactions (Aboagye et al., 2023). Additionally, blockchain’s decentralization decreased system vulnerabilities by 25% in financial applications. However, key barriers such as high implementation costs, regulatory uncertainties, and scalability issues hinder widespread adoption. Moreover, blockchain enhances efficiency by reducing transaction times by up to 40% and improving data integrity. Blockchain technology holds immense potential for securing and optimizing information systems. Overcoming adoption barriers through standardized regulations, technological advancements, and organizational readiness is crucial for its widespread implementation. Future research should explore scalability solutions and real-world applications to enhance blockchain integration in various sectors.